Private Foreign Investment in Pakistan (Notes & Comments) (The Pakistan Development Review, 1970)
Private foreign investment in Pakistan is regulated by the government's statement of industrial policy issued in 1959 which recognises, welcomes, and facilitates the inflow of private foreign investment in the country. In order to attract foreign investors, the government offers liberal incentives and concessions. In addition all profits are repatriable at the official rate of exchange. An attempt has been made in this note to determine the size and nature of private foreign investment in relation to the rest of the economy and to examine the inflows of private investment and remittances of profits, dividends, etc., made abroad.